Indaziflam Effect on Bermudagrass (Cynodon dactylon L. Pers.) Shoot Growth and Root Initiation as Influenced by Soil Texture and Organic Matter. Issue 1 (1st January 2015) - Schneider, Joseph G.; Haguewood, John B.; Song, Enzhan; Pan, Xiaowei; Rutledge, James M.; Monke, Bruce J.; Myers, Don F.; Anderson, Stephen H.; Ellersieck, Mark R.; Xiong, Xi
ABSTRACT: Indaziflam is an alkylazine herbicide used for preemergence control of annual weeds in warm‐season turfgrass. Growth chamber studies were conducted to determine the effect of indaziflam rate on bermudagrass ( Cynodon dactylon L. Pers.) shoot and root initiation as influenced by soil texture and organic matter (OM). Bermudagrass plants propagated from stolons were planted in five different growing media, including pure sand (100% sand), sand (92% sand, 6% clay) with or without OM (2%), and loamy sand (82% sand, 12% clay) with or without OM (2%). Indaziflam at rates of 48 or 16 g ha −1 followed by drenches of 2.5 cm of water were applied to the bermudagrass plants after maximal root length reached 30 cm. Bermudagrass growing in pure sand, regardless of indaziflam rate, showed the most injury, with root and shoot biomass reduced to <10 and <32%, respectively, compared with the nonherbicide‐treated control 38 d after treatment (DAT). Increase in clay content and addition of OM at 16 g ha −1 indaziflam significantly improved root biomass to ≥40% at 38 DAT. Despite inhibitions to root growth, aboveground tissues of plants growing in sand and loamy sand with OM showed minimal or no changes in turf color and coverage at 16 g ha −1 indaziflam. Results of this study indicate that small amounts of clay and OM in sandy soil aid in reducing bermudagrass phytotoxicity risk of 16 g ha −1 indaziflam.